EFEITO DE PRODUTOS ALTERNATIVOS in vitro E EM CASA DE VEGETAÇÃO NO CONTROLE DE Colletotrichum graminicola - Jacques, Filipe Lemos (2015)
The anthracnose of corn caused by Colletotrichum graminicola can occur both on leaves and stems of the plant and can cause extensive damage to the culture. In search of alternatives to the use of fungicides associated with the use of resistant varieties, main disease control method, the objective of this study was to evaluate the potential of control of C. graminicola in in vitro tests and the induction of resistance in corn plants in greenhouse conditions using different products abiotic and biotic. For in vitro tests were tested foliar fertilizer High Roots®, V6®, Maxi Flor®, Max Fruit®, Foskalium® 30-20 and manganese phosphite, the Ascophyllum nodosum extract (Acadian®), organic products Bacillus subtilis (Serenade®) and Bacillus thuringiensis (Dipel WP®) and control (without adding products). The products were incorporated into the oat medium melting at concentrations of 1, 10, 100 and 1000 ppm, which was added to the center of Petri dishes a fungi mycelium plug. The treatment control consisted of petri dishes without the incorporation of the treatments with a pathogen mycelial plug in the center. Daily was determined the diameter of the colonies to assess the mycelial growth of the fungus. With the data we calculated the percentage of inhibition of mycelial growth and the mycelial growth rate index. The treatment with B. thuringiensis and B. subtilis were the only ones that controlled at 100% the development of C. graminicola. Other treatments had total control at the dose of 1000 ppm. In tests in the greenhouse, in addition to the treatments used in vitro at concentrations that presented greater control, it was added acibenzolar-S-methyl (Bion®), which were sprayed on corn plants in V4 stage. After 72 hours of spraying the treatments was sprayed a suspension of spores of C. graminicola and after the first appearance of lesions were evaluated the severity and number of 2 cm lesions on the leaves. These data were calculated area under the disease progress curve and the area under the curve for infection frequency. The only treatment which controlled the disease was acibenzolar-S-methyl.